Multistage heterostructure composite aerogel, preparation method and application
Patent Information
- Application Number
- CN202611508417.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
气凝胶内部的孔隙结构能够提供污染物传质通道,其表面官能团和缺陷位点能够提供一定的吸附位点,但部分吸附材料在使用过程中存在结构稳定性不足、循环使用后吸附性能下降以及吸附完成后固液分离不便等问题
本发明通过对镍铁氧体依次进行多巴胺聚合和氨基化改性,在镍铁氧体颗粒表面构建出含有大量氨基的交联反应活性位点。多巴胺兼具超强粘附性和丰富活性基团,可在镍铁氧体表面形成均匀致密的有机过渡壳层,完美衔接无机镍铁氧体基体与后续APTES改性层,解决了传统无机硅壳层与镍铁氧体基体兼容性差、包覆不均匀和易剥离的核心问题,大幅提升核壳结构的整体稳定性,从而减少磁性颗粒在复合、冻干及热解过程中的团聚、迁移和局部富集。
Smart Images

Figure CN122999083A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite material technology, and in particular to multi-level heterogeneous composite aerogels, their preparation methods, and applications. Background Technology
[0002] With the rapid development of electronic communication, radar detection, and high-frequency electronic equipment, the electromagnetic radiation environment is becoming increasingly complex, placing higher demands on lightweight and efficient electromagnetic wave absorbing materials. Carbon-based aerogels, characterized by low density, high porosity, large specific surface area, and abundant internal transmission paths, provide porous spaces for the propagation and attenuation of electromagnetic waves, thus being widely used in the research of electromagnetic wave absorbing materials. Two-dimensional materials such as graphene and MXene have high electrical conductivity and strong dielectric response; introducing them into aerogel systems can improve the dielectric loss capability of the material. If graphene or MXene is used alone, the material's loss form for electromagnetic waves will be singular, and the bandwidth will be limited. Combining the two can complement each other's loss bands, broadening the effective absorption bandwidth. In addition, the staggered stacking of the two two-dimensional material sheets forms a large number of heterogeneous contact interfaces, causing the incident electromagnetic waves to be repeatedly reflected, refracted, and scattered within the material, significantly extending the propagation attenuation path and thus improving energy dissipation efficiency. However, the presence of only two-dimensional conductive materials in the absorbing material can easily lead to excessively high dielectric parameters, causing strong reflection of incident electromagnetic waves at the material surface, which is not conducive to impedance matching and broadband absorption.
[0003] To increase magnetic loss, existing technologies typically introduce magnetic particles such as nickel ferrite into carbon-based or two-dimensional aerogels, improving electromagnetic wave attenuation through the combined effect of magnetic and dielectric losses. However, inorganic magnetic nanoparticles such as nickel ferrite have high surface energy and are prone to aggregation in composite systems, exhibiting limited interfacial compatibility with carbon materials, two-dimensional sheet materials, or polymer matrices. During aerogel molding, drying, and subsequent high-temperature processing, magnetic particles may also experience local enrichment, migration, or interfacial separation, making it difficult for magnetic components to maintain a uniform distribution within the three-dimensional network. This, in turn, affects the coordination between dielectric loss, magnetic loss, and interfacial polarization within the material.
[0004] To improve the dispersibility and interfacial bonding properties of magnetic particles, existing technologies have employed methods such as inorganic coating, silane coupling agent modification, and organic layer coating to treat the surface of magnetic particles. However, the compatibility between different surface modification layers and magnetic particles, two-dimensional materials, and polymer components varies. Some modified systems also suffer from problems such as numerous processing steps, insufficient uniformity of the coating layer, and the tendency for modified particles to aggregate during subsequent composite processes. Especially for aerogel systems containing multiple components such as magnetic particles, graphene, MXene, and polymer precursors, the interfacial bonding state and spatial distribution between different components further affect the molding stability of the aerogel and its microstructure after high-temperature treatment.
[0005] Existing polymer-based aerogels typically utilize polyimide or its precursors to construct a three-dimensional support network, which is then combined with conductive or magnetic fillers to improve the structural stability and electromagnetic response performance of the aerogel. However, in multi-component composite systems, balancing the dispersion of two-dimensional sheets, the fixation of magnetic particles, and the integrity of the three-dimensional porous network remains challenging. Simple mixing of components easily leads to localized agglomeration, uneven pore structure, and insufficient number and bonding of interfaces. Furthermore, variations in the proportions of different conductive and magnetic phases cause changes in dielectric and magnetic parameters, making it difficult to achieve a good balance between attenuation capability and impedance matching.
[0006] On the other hand, porous carbon materials, graphene materials, and magnetic composite materials have also been applied to the adsorption of dyes in water. The porous structure inside aerogels can provide mass transfer channels for pollutants, and their surface functional groups and defect sites can provide certain adsorption sites. However, some adsorption materials suffer from insufficient structural stability during use, decreased adsorption performance after recycling, and inconvenient solid-liquid separation after adsorption. Existing research on composite aerogels mainly focuses on single applications such as electromagnetic wave absorption or pollutant adsorption. There is still room for further improvement in material systems that can maintain a stable porous structure while considering performance in different applications.
[0007] Therefore, how to improve the interfacial compatibility and dispersion stability between magnetic particles and two-dimensional materials and polymer components, enhance the integrity of the three-dimensional network of multi-component aerogels, and rationally coordinate the relationship between conductive components, magnetic components and multiphase interfaces, while improving the applicability of materials in recycling and separation, remains a technical problem to be solved in the field of composite aerogel materials. Summary of the Invention
[0008] Based on the technical problems existing in the background technology, this invention proposes a multi-level heterogeneous composite aerogel, its preparation method and application. The obtained composite aerogel has a three-dimensional porous network and a multi-component composite structure, and can be used for electromagnetic wave absorption and methylene blue adsorption.
[0009] The present invention proposes a method for preparing a multi-level heterogeneous composite aerogel, the steps of which are as follows: S1: Nickel ferrite was subjected to dopamine polymerization and amination modification in sequence to obtain amination-modified polydopamine-coated nickel ferrite particles. S2: Polymerize 2,2-bis[4-(4-aminophenoxy)phenyl]propane with 3,3′,4,4′-biphenyltetracarboxylic dianhydride in N,N-dimethylformamide, and obtain polyamic acid by washing and drying; S3: Polyamic acid and triethylamine are mixed in water to obtain a polyamic acid salt solution; graphene oxide, monolayer MXene, polyvinylpyrrolidone and the amino-modified polydopamine-coated nickel ferrite particles are dispersed in water to obtain a dispersion; the polyamic acid salt solution and the dispersion are mixed and a crosslinking agent is added to obtain a composite precursor solution, which is then subjected to vacuum freeze-drying and pyrolysis under an inert atmosphere to obtain a multi-level heterostructure composite aerogel.
[0010] Preferably, the preparation method of nickel ferrite is as follows: ferric nitrate nonahydrate, nickel nitrate hexahydrate and ethylene glycol are dispersed in water, and sodium acetate and polyvinylpyrrolidone are added to react. After the reaction, the mixture is washed and dried to obtain nickel ferrite. The mass ratio of ferric nitrate nonahydrate, nickel nitrate hexahydrate, sodium acetate, and polyvinylpyrrolidone is 1.0-2.3:0.35-0.80:2.2-4.6:1; The reaction conditions are a temperature of 160-200℃ and a time of 12-24h.
[0011] Preferably, the method for dopamine polymerization includes the following steps: dispersing nickel ferrite in water, adding Tris buffer and dopamine hydrochloride, reacting in the dark, washing and drying to obtain polydopamine-coated nickel ferrite; The mass ratio of nickel ferrite to dopamine hydrochloride is 3.75-6.25:1; The conditions for the light-protected reaction are a temperature of 25-30℃ and a time of 12-36 hours.
[0012] Preferably, the amination modification method includes the following steps: dispersing the dopamine-polymerized nickel ferrite in anhydrous ethanol, adding 3-aminopropyltriethoxysilane and heating under reflux, and then washing and drying to obtain amino-modified polydopamine-coated nickel ferrite particles. The mass-to-volume ratio of dopamine-polymerized nickel ferrite to 3-aminopropyltriethoxysilane is 1g:3-5ml; The reaction conditions are a temperature of 60℃-78℃ and a time of 6-18h.
[0013] Preferably, the preparation method of monolayer MXene is as follows: LiF is dispersed in hydrochloric acid, and then Ti3AlC2 is added to react. After the reaction, the mixture is washed, sonicated, centrifuged and dried to obtain monolayer MXene. The mass ratio of LiF to Ti3AlC2 is 1-2:1; The reaction conditions are a temperature of 40-60℃ and a time of 12-36h.
[0014] Preferably, the mass ratio of 2,2-bis[4-(4-aminophenoxy)phenyl]propane to 3,3′,4,4′-biphenyltetracarboxylic dianhydride in S2 is 1:1-2, and the reaction conditions are ice bath conditions for 2-4 hours. The mass ratio of graphene oxide, monolayer MXene, polyvinylpyrrolidone, amino-modified polydopamine-coated nickel ferrite particles, polyamic acid, and crosslinking agent in S3 is 0.065-0.095:0.03-0.06:0.01-0.04:0-0.08:0.45-1.25:0.05-0.35, and the amount of amino-modified polydopamine-coated nickel ferrite particles added is not zero; the pyrolysis treatment conditions are a temperature of 700-800℃, a time of 1-3h, and a heating rate of 1-3℃ / min; the crosslinking agent is one or more of glutaraldehyde, epichlorohydrin, and 1,4-bis(glycidoxy)butane.
[0015] The present invention proposes a multi-level heterogeneous composite aerogel, which is prepared by the above-described preparation method.
[0016] Preferably, the composite aerogel has a continuous three-dimensional porous network framework structure, in which NC / NFO particles are dispersed, and the NC / NFO particles have a core-shell structure; the composite aerogel contains FeNi alloy phase and Fe2O3 phase.
[0017] The present invention proposes the application of the above-mentioned multi-level heterogeneous composite aerogel in electromagnetic wave absorption.
[0018] The present invention relates to the application of the above-mentioned multi-level heterostructure composite aerogel in methylene blue adsorption.
[0019] Beneficial technical effects of the present invention: This invention modifies nickel ferrite by sequentially polymerizing and amination with dopamine, constructing cross-linking reactive sites containing a large number of amino groups on the surface of nickel ferrite particles. Dopamine possesses both strong adhesion and abundant active groups, forming a uniform and dense organic transition shell on the surface of nickel ferrite. This shell perfectly connects the inorganic nickel ferrite matrix with the subsequent APTES modified layer, solving the core problems of poor compatibility, uneven coating, and easy peeling of traditional inorganic silicon shells with nickel ferrite matrices. This significantly improves the overall stability of the core-shell structure, thereby reducing the agglomeration, migration, and local enrichment of magnetic particles during composite, freeze-drying, and pyrolysis processes.
[0020] This invention constructs a composite precursor system by co-constructing nickel ferrite particles coated with polyamic acid salts, graphene oxide, MXene, and amino-modified polydopamine, and cross-links them with glutaraldehyde to maintain a stable spatial distribution of the components before freeze-drying. After freeze-drying and inert atmosphere pyrolysis, the organic components are carbonized, the graphene oxide is reduced, and the magnetic and titanium-based components undergo phase transformation, ultimately forming a multi-level heterogeneous structure with a continuous, interconnected three-dimensional porous carbonaceous framework, core-shell magnetic particles, and multiple phases such as FeNi and Fe2O3. This structure can further enhance the interfacial bonding between different functional components, improve the overall structural stability of the composite aerogel, and provide a stable multifunctional structural basis for electromagnetic wave dissipation and pollutant adsorption.
[0021] This multi-component composite aerogel can solve problems such as the easy stacking of single MXene sheets, the easy collapse of graphene oxide framework, and the disordered pores of polyamic acid carbon-based aerogels. While optimizing the pore structure and improving structural stability, it also provides the prerequisites for achieving synergistic electromagnetic loss through multiple mechanisms and ultra-wideband high-efficiency microwave absorption. The above structure allows magnetic loss (nickel ferrite), dielectric loss (MXene / reduced graphene), polarization loss (nitrogen-doped carbon, amino active sites), and interfacial polarization loss (multi-component heterogeneous interface) to work together in the same material system. At the same time, the dielectric parameters, magnetic parameters, and impedance matching are coordinated by the amount of magnetic components added, avoiding impedance mismatch caused by simply increasing conductive or magnetic components. This allows the material to achieve attenuation capability and a wide effective absorption bandwidth for electromagnetic waves across the entire S, C, X, and Ku bands even at relatively thin thicknesses.
[0022] Furthermore, the composite aerogel obtained in this invention also possesses pollutant adsorption capabilities. The three-dimensional porous network formed after pyrolysis provides channels for the diffusion and transport of methylene blue molecules. The aromatic structures, nitrogen-containing structures, oxygen-containing groups, and metal-related active sites in the carbonaceous skeleton can all participate in methylene blue adsorption, making the adsorption process simultaneously influenced by multiple mechanisms such as pore structure enrichment, π-π interactions, electrostatic interactions, hydrogen bonding, and interfacial coordination, thereby improving the material's adsorption capacity and stability for methylene blue. Simultaneously, the magnetic components in the composite aerogel enable rapid separation of the adsorbed material using an external magnetic field, allowing for reuse after desorption treatment, reducing the difficulty of adsorbent material recovery and solid-liquid separation.
[0023] Therefore, this invention simultaneously constructs electromagnetic energy dissipation channels, dye adsorption sites, and magnetic separation units within the same multi-level heterogeneous structure, enabling the resulting composite aerogel to possess electromagnetic wave absorption, methylene blue adsorption, and magnetic separation and recovery properties, thereby improving the functional integration and application value of multi-component composite aerogels. Attached Figure Description
[0024] Figure 1 This is a schematic diagram of the preparation process of the multi-level heterostructure composite aerogel proposed in this invention; Figure 2 The structure of the multi-level heterostructure composite aerogel proposed in this invention is characterized, wherein (a) is the IR spectrum, (b) is the XRD spectrum, (c) is the Raman spectrum, and (d) is the VSM spectrum. Figure 3 The XPS energy spectrum of S2 proposed in this invention is shown below; where (a) is the full spectrum, (b) is the C1s fine spectrum, (c) is the N1s fine spectrum, (d) is the O1s fine spectrum, (e) is the Ti2p fine spectrum, (f) is the Ni2p fine spectrum, (g) is the Fe2p fine spectrum, and (h) is the Si2p fine spectrum. Figure 4 The images shown are SEM and EDS images proposed in this invention; where (a) is the SEM morphology image of NFO, (b) is the SEM morphology image of NH2-PDA@NFO, (ce) is the SEM morphology image of S2 at different sizes, and (fl) are the EDS images of C, N, O, Si, Ti, Fe and Ni of S2 respectively. Figure 5 The images are TEM and HRTEM images of S2 proposed in this invention; where (a) is the TEM image at 200 nm, (b) is the TEM image at 50 nm, (c) is the HRTEM image of Ti2O3 in S2 at 5 nm, and (d) is the HRTEM image of FeNi and Fe2O3 in S2 at 5 nm. Figure 6 The electromagnetic parameters of the aerogels prepared in Examples 1-4 of this invention are shown in the figure; where (a) is the real part of the dielectric constant, (b) is the imaginary part of the dielectric constant, (c) is the real part of the permeability, (d) is the imaginary part of the permeability, (e) is the dielectric loss tangent, and (f) is the magnetic loss tangent. Figure 7 The diagram shows the reflection loss and 2D contour plot of the aerogel proposed in this invention; where (ab) is S0, (cd) is S1, (ef) is S2, and (gh) is S3. Figure 8 The above are the electromagnetic wave absorption performance parameter analysis graphs proposed in this invention; where (a) is the attenuation constant curve, (b) is the C0-f curve, (c) is the impedance matching curve, and (d) is the Cole-Cole curve. Figure 9 This is a schematic diagram of the electromagnetic wave absorption mechanism of the multi-level heterostructure composite aerogel proposed in this invention. Figure 10Electromagnetic parameter diagrams of the aerogels prepared in Example 3 and Comparative Examples 1-4 of this invention are provided; wherein (a) is the real part of the dielectric constant, (b) is the imaginary part of the dielectric constant, (c) is the real part of the permeability, (d) is the imaginary part of the permeability, (e) is the dielectric loss tangent, and (f) is the magnetic loss tangent. Figure 11 The diagrams are the reflection loss map and 2D contour map proposed in this invention; where (ab) represents NC / NFOPDA / MX / rGO, (cd) represents C / NFO / MX / rGO, (ef) represents NC / NFO / MX, and (gh) represents NC / NFO / rGO. Figure 12 The Cole-Cole curves proposed in this invention are shown below; where (a) is NC / NFOPDA / MX / rGO, (b) is C / NFO / MX / rGO, (c) is NC / NFO / MX, and (d) is NC / NFO / rGO. Figure 13 The diagram shows the electromagnetic wave absorption performance parameters proposed in this invention; where (a) is the C0-f curve, (b) is the impedance matching curve, and (c) is the attenuation constant curve. Figure 14 The effects of the adsorption conditions proposed in this invention on the adsorption performance of S2 on MB; wherein (a) is the effect of MB concentration at different temperatures on the adsorption performance of S2, (b) is the effect of adsorption time at different MB concentrations on the adsorption performance of S2, (c) is the effect of the pH of the MB solution on the adsorption performance of S2, and (d) is the effect of the amount of adsorbent on the adsorption performance of S2. Figure 15 The adsorption isotherm, kinetics and cyclic regeneration performance of S2 on MB proposed in this invention are shown in (a) Freundlich model, (b) Langmuir model, (c) relationship between lnkd and 1 / T, (d) pseudo-first-order kinetic model, (e) pseudo-second-order kinetic model, and (f) adsorption-desorption cycle of S2 on MB. Figure 16 The XPS and IR spectra of MB after S2 adsorption proposed in this invention are shown; where (a) is the C1s fine spectrum, (b) is the O1s fine spectrum, (c) is the N1s fine spectrum, and (d) is the IR spectrum. Figure 17 This is a schematic diagram of the mechanism of S2 adsorption of MB proposed in this invention. Detailed Implementation
[0025] The present invention will be further explained below with reference to specific embodiments.
[0026] Example 1 12 mol / L hydrochloric acid (20 mL) was added to a 100 mL polytetrafluoroethylene beaker, followed by 1.6 g of LiF powder. The mixture was stirred for 10 min until completely dissolved. 1.0 g of Ti3AlC2 powder (400 mesh) was added in batches, and the mixture was placed in a 50 °C water bath for 24 h. After the reaction, the mixture was washed twice with 1.0 mol / L hydrochloric acid aqueous solution, and then washed with deionized water until the pH of the supernatant was neutral. Under nitrogen protection, the gray precipitate was sonicated in ice water for 2 h. The black mixture was then centrifuged, and the upper black liquid was freeze-dried to obtain a black-green monolayer MXene.
[0027] To a 200 mL beaker, add 2 mmol of ferric nitrate nonahydrate, 1 mmol of nickel nitrate hexahydrate, 40 mL of ethylene glycol, and 40 mL of deionized water sequentially, and stir magnetically for 30 min. Weigh 1.7 g of sodium acetate and 0.5 g of polyvinylpyrrolidone (PVP) using an analytical balance and add them to the above solution, continuing stirring for another 30 min. Transfer the mixture to a reaction vessel and react at 180 °C for 18 h. After the reaction is complete, wash with deionized water and anhydrous ethanol, respectively. Finally, centrifuge and vacuum dry to obtain nickel ferrite, denoted as NFO.
[0028] Add 0.3 g of NFO powder and 200 mL of deionized water to a 500 mL beaker. After ultrasonic dispersion in an ice bath for 40 min, a brown suspension is formed. Then, add 0.3 g of Tris buffer and 0.06 g of dopamine hydrochloride (DA·HCl) in sequence. Incubate the mixture at 25 °C in the dark for 24 h. After the reaction, wash the mixture alternately with deionized water and anhydrous ethanol until the centrifuged liquid is clear. Finally, centrifuge and freeze dry to obtain polydopamine-coated nickel ferrite, denoted as NFO@PDA.
[0029] NFO@PDA (0.2 g) and 80 mL of anhydrous ethanol were added to a 150 mL three-necked flask and sonicated for 60 min. Under nitrogen protection, 0.75 mL of 3-aminopropyltriethoxysilane (APTES) was added and the mixture was heated under reflux for 12 h. After the reaction was completed, the mixture was washed alternately with deionized water and anhydrous ethanol until the centrifuged liquid became clear. Finally, after centrifugation and freeze drying, amino-modified polydopamine-coated nickel ferrite was obtained, denoted as NFO@PDA-NH2.
[0030] Under ice bath conditions, 4.00 g of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) and 80 mL of N,N-dimethylformamide (DMF) were added to a 150 mL three-necked flask, and the mixture was mechanically stirred until BAPP was completely dissolved. Then, 5.87 g of 3,3′,4,4′-biphenyltetracarboxylic dianhydride (BPDA) was added to the solution in three batches. After the addition was complete, the reaction was continued for 3 hours, and the reaction system became a pale yellow viscous liquid. The reaction solution was slowly poured into 500 mL of ice water, and the mixture was vacuum filtered to obtain a white solid, which was then freeze-dried to obtain polyamic acid, denoted as PAA.
[0031] 2.0 g of PAA powder was dispersed in 10 mL of deionized water, and 3.5 mL of triethylamine (TEA) was slowly added dropwise. After the addition was complete, the mixture was stirred for 2 h to obtain a homogeneous transparent polyamic acid salt solution (PAAs), denoted as solution A. 160 mg of graphene oxide (GO), 80 mg of MXene, and 50 mg of polyvinylpyrrolidone (PVP) were added to a 50 mL beaker and ultrasonically dispersed for 60 min, denoted as dispersion B. Dispersion A was poured into solution B, and 0.2 mL of glutaraldehyde was added. The mixture was stirred vigorously for 1 h. The homogeneous solution was poured into a mold, frozen, and then freeze-dried under vacuum for 24 h to obtain the composite aerogel precursor. Finally, the composite aerogel precursor was heated to 750 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and pyrolyzed at this temperature for 2 h to obtain the final product, denoted as S0.
[0032] Example 2 2.0 g of PAA powder was dispersed in 10 mL of deionized water, and 3.5 mL of TEA was slowly added dropwise. After the addition was complete, the mixture was stirred for 2 h to obtain homogeneous transparent PAAs, which was denoted as solution A. 160 mg of GO, 80 mg of MXene, and 50 mg of PVP were added to a 50 mL beaker and ultrasonically dispersed for 30 min. Then, 50 mg of NFO@PDA-NH2 nanoparticles were added and ultrasonically dispersed for another 30 min, which was denoted as dispersion B. Dispersion A was poured into solution B, and 0.2 mL of glutaraldehyde was added. The mixture was stirred vigorously for 1 h. The homogeneous solution was poured into a mold, frozen, and then freeze-dried under vacuum for 24 h to obtain the composite aerogel precursor. Finally, the composite aerogel precursor was heated to 750 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and pyrolyzed at this temperature for 2 h to obtain the final product, denoted as S1.
[0033] Example 3 2.0 g of PAA powder was dispersed in 10 mL of deionized water, and 3.5 mL of TEA was slowly added dropwise. After the addition was complete, the mixture was stirred for 2 h to obtain homogeneous transparent PAAs, denoted as solution A. 160 mg of GO, 80 mg of MXene, and 50 mg of PVP were added to a 50 mL beaker and ultrasonically dispersed for 30 min. Then, 100 mg of NFO@PDA-NH2 nanoparticles were added and ultrasonically dispersed for another 30 min, denoted as dispersion B. Dispersion A was poured into solution B, and 0.2 mL of glutaraldehyde was added. The mixture was stirred vigorously for 1 h. The homogeneous solution was poured into a mold, frozen, and then freeze-dried under vacuum for 24 h to obtain the composite aerogel precursor. Finally, the composite aerogel precursor was heated to 750 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and pyrolyzed at this temperature for 2 h to obtain the final product, denoted as S2.
[0034] Example 4 2.0 g of PAA powder was dispersed in 10 mL of deionized water, and 3.5 mL of TEA was slowly added dropwise. After the addition was complete, the mixture was stirred for 2 h to obtain homogeneous transparent PAAs, denoted as solution A. 160 mg of GO, 80 mg of MXene, and 50 mg of PVP were added to a 50 mL beaker and ultrasonically dispersed for 30 min. Then, 150 mg of NFO@PDA-NH2 nanoparticles were added and ultrasonically dispersed for another 30 min, denoted as dispersion B. Dispersion A was poured into solution B, and 0.2 mL of glutaraldehyde was added. The mixture was stirred vigorously for 1 h. The homogeneous solution was poured into a mold, frozen, and then freeze-dried under vacuum for 24 h to obtain the composite aerogel precursor. Finally, the composite aerogel precursor was heated to 750 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and pyrolyzed at this temperature for 2 h to obtain the final product, denoted as S3.
[0035] Comparative Example 1 2.0 g of PAA powder was dispersed in 10 mL of deionized water, and 3.5 mL of TEA was slowly added dropwise. After the addition was complete, the mixture was stirred for 2 h to obtain homogeneous transparent PAAs, which was denoted as solution A. 160 mg of GO, 80 mg of MXene, and 50 mg of PVP were added to a 50 mL beaker and ultrasonically dispersed for 30 min. Then, 100 mg of NFO@PDA was added and ultrasonically dispersed for another 30 min, which was denoted as dispersion B. Dispersion A was poured into solution B, and 0.2 mL of glutaraldehyde was added. The mixture was stirred vigorously for 1 h. The homogeneous solution was poured into a mold, frozen, and then freeze-dried under vacuum for 24 h to obtain the composite aerogel precursor. Finally, the composite aerogel precursor was heated to 750 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and pyrolyzed at this temperature for 2 h to obtain the final product, denoted as NC / NFO-PDA / MX / rGO.
[0036] Comparative Example 2 2.0 g of PAA powder was dispersed in 10 mL of deionized water, and 3.5 mL of TEA was slowly added dropwise. After the addition was complete, the mixture was stirred for 2 h to obtain homogeneous transparent PAAs, which was denoted as solution A. 160 mg of GO, 80 mg of MXene, and 50 mg of PVP were added to a 50 mL beaker and ultrasonically dispersed for 30 min. Then, 100 mg of NFO was added and ultrasonically dispersed for another 30 min, which was denoted as dispersion B. Dispersion A was poured into solution B, and 0.2 mL of glutaraldehyde was added. The mixture was stirred vigorously for 1 h. The homogeneous solution was poured into a mold, frozen, and then freeze-dried under vacuum for 24 h to obtain the composite aerogel precursor. Finally, the composite aerogel precursor was heated to 750 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and pyrolyzed at this temperature for 2 h to obtain the final product, denoted as C / NFO / MX / rGO.
[0037] Comparative Example 3 2.0 g of PAA powder was dispersed in 10 mL of deionized water, and 3.5 mL of TEA was slowly added dropwise. After the addition was complete, the mixture was stirred for 2 h to obtain homogeneous transparent PAAs, which was denoted as solution A. 240 mg of MXene and 50 mg of PVP were added to a 50 mL beaker, and the mixture was ultrasonically dispersed for 30 min. Then, 100 mg of NFO@PDA-NH2 nanoparticles were added, and the mixture was ultrasonically dispersed for another 30 min, which was denoted as dispersion B. Dispersion A was poured into solution B, and 0.2 mL of glutaraldehyde was added. The mixture was stirred vigorously for 1 h. The homogeneous solution was poured into a mold, frozen, and then freeze-dried under vacuum for 24 h to obtain the composite aerogel precursor. Finally, the composite aerogel precursor was heated to 750 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and pyrolyzed at this temperature for 2 h to obtain the final product, denoted as NC / NFO / MX.
[0038] Comparative Example 4 2.0 g of PAA powder was dispersed in 10 mL of deionized water, and 3.5 mL of TEA was slowly added dropwise. After the addition was complete, the mixture was stirred for 2 h to obtain homogeneous transparent PAAs, denoted as solution A. 240 mg of GO and 50 mg of PVP were added to a 50 mL beaker, and the mixture was ultrasonically dispersed for 30 min. Then, 100 mg of NFO@PDA-NH2 nanoparticles were added, and the mixture was ultrasonically dispersed for another 30 min, denoted as dispersion B. Dispersion A was poured into solution B, and 0.2 mL of glutaraldehyde was added. The mixture was stirred vigorously for 1 h. The homogeneous solution was poured into a mold, frozen, and then freeze-dried under vacuum for 24 h to obtain the composite aerogel precursor. Finally, the composite aerogel precursor was heated to 750 °C at a heating rate of 2 °C / min in a nitrogen atmosphere and pyrolyzed at this temperature for 2 h to obtain the final product, denoted as NC / NFO / rGO.
[0039] The structures of the products prepared in Examples 1-4 were characterized, and the results are as follows: Figures 2-5 As shown.
[0040] In the infrared spectrum (IR) of NH-PDA@NFO ( Figure 2 In part (a), 3382-3241cm -1 The broad peak at 293 cm⁻¹ originates from the overlap of absorption peaks due to the stretching vibrations of OH and NH. -1 The absorption peak at 1642 cm⁻¹ is caused by the symmetric stretching vibration of -CH₂. -1 and 768cm -1 These correspond to the in-plane and out-of-plane bending vibrations of -NH2, respectively. 624 cm -1 803cm -1 and 1043cm -1 The absorption peaks at 1116 cm⁻¹ correspond to the bending vibration, symmetric stretching vibration, and asymmetric stretching vibration of Si-O-Si, respectively. -1 1185cm -1 and 1223cm -1 These are the CO stretching vibration peak, the C-Si-O asymmetric stretching vibration peak, and the CN stretching vibration peak, respectively. (515 cm⁻¹) -1 The peaks represent the stretching vibrations of the NO and Fe-O metal-oxygen bonds. These results indicate that amino groups have been successfully modified onto the NFO surface.
[0041] In the IR spectrum of MX / rGO / PAAs, 1504 cm⁻¹ -1 This is the vibrational peak of the C=C skeleton in GO and PAA. 1461cm -1 and 1720cm -1 -COO - The characteristic absorption peak of amides is observed at 1325 cm⁻¹, along with the symmetric stretching vibration peak of C=O in -COOH. -1 1593cm -1 and 1638cm -1 These correspond to CN stretching vibration, NH bending (amide II band), and C=O stretching (amide I band), respectively. 613 cm -1 637cm -1 and 1122cm -1 These are the vibrational peaks of Ti-O, the bending vibration peak of CO, and the stretching vibration peak of CO in MXene, respectively.
[0042] Compared to NH2-PDA@NFO and MX / rGO / PAAs, the IR spectrum of the S2 composite aerogel precursor (NH2-PDA@NFO / MX / rGO / PAAs) shows a higher 1602 cm⁻¹. -1 The newly appearing peak is a C=N stretching vibration peak. 1217cm -1The stretching vibration of CN at this site is significantly enhanced compared to MX / rGO / PAAs and NH2-PDA@NFO. These results indicate that NH2-PDA@NFO / MX / rGO / PAAs have been successfully prepared.
[0043] During high-temperature pyrolysis, the organic functional groups such as hydroxyl, amide, and carboxyl groups in NH2-PDA@NFO / MX / rGO / PAAs undergo cleavage and removal. Simultaneously, the organic components are gradually carbonized and reconstructed into a nitrogen-doped carbon framework. Furthermore, the inorganic NFO is coated by the carbon matrix, and its structural structure becomes more compact, resulting in an overall decrease in the intensity of the infrared absorption peaks corresponding to various functional groups in S2. (1493 cm⁻¹) -1 For the vibration of the conjugated aromatic ring C=C skeleton, 1466 cm⁻¹ -1 and 1593cm -1 : These are COO-symmetric and antisymmetric stretching vibrations, respectively, 1263 cm⁻¹ -1 1319cm -1 1418cm -1 and 1621cm -1 These are the stretching vibrations of aryl CN, amide CN, heterocyclic CN, and conjugated C=N, respectively. 1079 cm⁻¹ -1 and 1112cm -1 These represent the Si-O-Si asymmetric stretching and CO stretching vibrations, respectively. 1356 cm⁻¹ -1 and 1388cm -1 These represent the defect peaks of carbon materials and the CH bending vibrations, respectively.
[0044] The phase composition of S0-S3 was analyzed by X-ray diffraction (XRD), and the results are as follows: Figure 2 As shown in part (b), the broadened peak at 2θ = 20~25° of S0 is a characteristic diffraction peak of amorphous carbon. In the XRD patterns of S1-S3, the diffraction peaks at 43.71°, 50.96° and 74.94° correspond to the (111), (200) and (220) crystal planes of FeNi alloy (JCPDS No. 09-3507), respectively. The diffraction peaks at 24.12°, 33.12°, 35.60°, 40.82°, 49.41°, 54.00°, 57.51° and 62.37° correspond one-to-one with the (012), (104), (110), (113), (024), (116), (018) and (214) diffraction peaks of Fe2O3 (JCPDS No. 89-0597). The above results indicate that highly crystalline Fe2O3 and FeNi alloy phases coexist in samples S1-S3. Furthermore, the intensity of the crystalline diffraction peaks in the samples gradually increases with increasing NFO content.
[0045] In Raman spectroscopy ( Figure 2 In part (c), peak D (1350 cm⁻¹) -1 ) and defects and disordered carbon (sp) in materials 3 Related to, G peak (1580cm) -1 ) and the graphitized carbon (sp) of the material 2 Related to the intensity ratio of peak D to peak G (I) D / I G The ratio reflects the degree of graphitization of the material and is a key parameter for controlling the dielectric constant, polarization loss, and impedance matching, directly determining the reflection loss (RL) and effective absorption bandwidth (EAB). D / I G A higher I value indicates a lower degree of graphitization in the material, more defects and polarization centers, but weaker electrical conductivity; conversely, a lower I value indicates a lower degree of graphitization. D / I G The smaller the value, the higher the degree of graphitization of the material, the fewer defects and polarization centers, but the stronger the conductivity. Calculations show that the I0 value for S0-S3... D / I G The value decreased from 1.07 to 0.94. This shows that as the NFO content in the aerogel increases, the graphitization degree of S0-S3 increases sequentially, defects and polarization centers decrease, but the electrical conductivity increases accordingly.
[0046] Vibrating Sample Magnetometer (VSM) spectra from S1-S3 ( Figure 2 From part (d), we can see that the saturation magnetization (M) s The value increases with the amount of NFO added. Specifically, the M value of S1, S2, and S3 increases with the amount of NFO added. s The values were 27.8 emu / g, 57.6 emu / g, and 81.5 emu / g, respectively. Coercivity (H c The flux density (FDC) increased significantly from 12.4 Oe to 305.4 Oe. This change is attributed to the enhanced magnetic dipole coupling and improved equivalent magnetic anisotropy caused by NFO particle agglomeration under high filling conditions. S1 exhibits extremely low coercivity and excellent efficiency in low-frequency natural resonance loss, but due to M... s The value is too low, resulting in insufficient contribution to overall magnetic loss; S3's M s The highest value indicates the strongest intrinsic magnetic loss potential; however, excessively high H values... c This causes the natural resonance to shift to higher frequencies, suppresses low-frequency magnetic losses, and the excessive magnetic phase disrupts the graphene conductive network, leading to weakened impedance matching; S2, on the other hand, possesses a moderate M... s Value and equilibrium H c Within the 2-18GHz frequency band, it can simultaneously activate efficient low-frequency natural resonance and mid-to-high frequency exchange resonance magnetic loss.
[0047] The chemical composition and elemental valence states of S2 were analyzed using X-ray photoelectron spectroscopy (XPS), and the results are as follows: Figure 3 As shown. In the full spectrum of S2 ( Figure 3 The presence of C, N, O, Ni, Fe, Ti and Si elements in (a) confirms that NH2-PDA@NFO and MX / rGO / PAAs have been cross-linked and incorporated into the three-dimensional network structure of the aerogel.
[0048] In the high-resolution C1s fine spectrum of S2 ( Figure 3 In part (b), five peaks are observed, corresponding to CC (284.4 eV), C=C (284.7 eV), CO (285.6 eV), CN (286.7 eV), and OC=O (289.5 eV). The fine spectrum of N1s ( Figure 3 Part (c) is fitted with four forms of N: pyridine nitrogen (399.3 eV), metal-coordinated nitrogen (MN) (400.1 eV), pyrrole nitrogen (401.3 eV), and graphitic nitrogen (401.6 eV). O1s fine spectrum ( Figure 3 The (d) portion can be decomposed into five characteristic peaks, corresponding to metal-oxygen (MO), metal-hydroxyl (M-OH), C=O, COC and adsorbed H2O, respectively, with binding energies of 529.7 eV, 530.5 eV, 531.8 eV, 532.6 eV and 533.7 eV.
[0049] In the Ti2p fine spectrum ( Figure 3 In part (e), there are four groups of Ti2p 1 / 2 With Ti2p 3 / 2 The two peaks correspond to Ti. 2+ (455.2 eV and 460.5 eV), Ti 3+ (457.8 eV and 462.6 eV), Ti-C (458.6 eV and 463.6 eV), and Ti-O (459.1 eV and 464.9 eV). The Ti2p vs. O1s plots confirm that the MXene component in S2 contains oxygen-containing end groups. This indicates that S2 contains abundant oxygen-containing functional groups, which contribute to polarization loss and thus enhance the absorption performance for EMW. (Ni2p fine spectrum) Figure 3 The (f) part shows three distinct double peaks, which are attributed to Ni respectively. 0 (853.8 eV and 870.5 eV), Ni 2 + (856.4 eV and 874.7 eV) and satellite peaks (Sat.) (847.8 eV and 860.9 eV). Similarly, the fine spectrum of Fe2p ( Figure 3In the (g) portion, the peaks at 707.7 eV and 720.4 eV correspond to Fe. 0 The peaks at 710.8 eV and 723.7 eV are attributed to Fe. 2+ 713.3 eV and 726.1 eV correspond to Fe 3+ In addition, there are two satellite peaks (717.5 eV and 730.1 eV).
[0050] NFO nickel ferrite (NFO) was examined by scanning electron microscopy (SEM). Figure 4 (a) of NH2-PDA@NFO Figure 4 (b) of the S2 ( Figure 4 The microstructure and structural features of the (ce) portion were characterized. NFO exhibited a typical nanoparticle stacking morphology, with smooth particle surfaces and inter-particle aggregation, resulting in a relatively simple overall micro-interface. After PDA and APTES coating modification, the surface of NH2-PDA@NFO particles became rougher and exhibited obvious angular structures, with the average particle size increasing from 75 nm to 125 nm. This demonstrates that the organic layer was successfully coated in situ onto the surface of the ferrite particles, effectively improving the surface properties and dispersibility of the magnetic particles and providing sufficient reactive sites for subsequent crosslinking with PAA, MXene, and GO.
[0051] from Figure 4 Part (c) shows that S2 constructs a continuous, interconnected three-dimensional porous network framework structure. The aerogel contains abundant hierarchical pores and a small number of structural defects; this porous structure is a typical characteristic of aerogel materials. The loose, porous three-dimensional network not only effectively reduces the overall density of the material but also generates multiple reflections, scattering, and attenuation effects when electromagnetic waves are incident, significantly extending the electromagnetic wave transmission path and significantly improving electromagnetic wave attenuation capability. NH2-PDA@NFO, PAAs, and glutaraldehyde undergo chemical cross-linking to form strong covalent bonds. Figure 4 part (d) and Figure 4 Part (e) shows that a large number of NC / NFO particles derived from the pyrolysis of NH2-PDA@NFO are uniformly embedded and dispersed within the aerogel framework, without obvious agglomeration or detachment. The organic layer on the NFO surface effectively improves the interfacial compatibility between the magnetic filler and the PAAs organic matrix, alleviating the interfacial impedance mismatch problem between the inorganic magnetic particles and the organic polymer matrix, providing a good microstructure basis for the excellent electromagnetic wave absorption performance of this composite material. EDS images show that S2 is composed of C, N, O, Si, Ti, Fe, and Ni elements. Figure 4(fl portion). The results show that PDA and APTES were successfully coated on the NFO surface. The Ti element around NC / NFO indicates that MXene and PAAs together serve as the scaffold structure of the aerogel.
[0052] In the TEM image of S2 ( Figure 5 (Parts (a) and (b)) show a large number of NC / NFO particles uniformly distributed within the aerogel. HRTEM images ( Figure 5 Part (c) clearly shows the complex heterogeneous interface structure inside the aerogel. In the lower left region, distinct fan-shaped lattice fringes are observed with a lattice spacing of 0.375 nm, corresponding to the (012) crystal plane of Ti₂O₃. The presence of this localized crystalline phase confirms that during the aerogel construction process, Ti atoms on the MXene surface detach from the framework and combine with oxygen in the environment, forming Ti oxides in situ. This tight heterogeneous interface facilitates rapid electron transfer between different components. Furthermore, the phase interface between graphitic carbon and NC / NFO (marked with white lines) indicates that the heterogeneous interface has been successfully formed. Figure 5 Part (d) shows that S2 has a core-shell structure (marked with yellow lines), confirming that the organic layer has been successfully attached to the NFO surface. The thickness of this shell coating is approximately 4 nm. The interplanar spacings in S2 are 0.207 nm and 0.270 nm, corresponding to the (111) crystal plane of FeNi and the (104) crystal plane of Fe2O3, respectively, which are consistent with the XRD analysis results.
[0053] The microwave absorption properties of the products prepared in Examples 1-4 and Comparative Examples 1-4 were tested, and the results are as follows: Figures 6-13 As shown.
[0054] The electromagnetic parameters, including the relative complex permittivity (ε), were measured in the 2-18 GHz frequency range using a vector network analyzer (VNA) via the coaxial line method. r =ε'-jε'') and relative complex permeability (μ r =μ'-jμ''). Before testing, the prepared aerogel and paraffin were uniformly mixed with a filler content of 10%, and then pressed into a ring structure with an outer diameter of 7.0 mm, an inner diameter of 3.04 mm, and a thickness of 2.0 mm.
[0055] The spectrum of the real part of the dielectric constant (ε') as a function of frequency (f) Figure 6As shown in part (a), the ε' of S0, S1, S2, and S3 decreased from 14.05 to 9.18, from 12.23 to 7.99, from 9.33 to 7.51, and from 8.50 to 6.84, respectively. This may be due to the polarization process of the material lagging behind the change of the alternating electric field, resulting in a dispersion effect. On the other hand, with the increase of NH2-PDA@NFO content, the ε' of S0-S3 decreased significantly. This is because GO and MXene are both two-dimensional highly conductive materials, which will form strong electronic polarization and interfacial polarization, resulting in a higher ε' of S0; while NH2-PDA@NFO, as a magnetic ceramic phase, has a much lower conductivity than GO and MXene. With the increase of NH2-PDA@NFO addition, the relative content of GO and MXene in the system decreases, the conductive network is diluted, the polarization intensity weakens, and ultimately the ε' decreases.
[0056] Figure 6 Part (b) shows the trend of the imaginary part ε'' of the dielectric constant of S0-S3 with the change of f. Since both conduction loss and polarization loss decrease at high frequencies, ε'' of S0-S3 decreases slowly with the increase of f. The trend of ε'' is similar to that of ε' with the content of NH2PDA@NFO, that is, as the content of NH2PDA@NFO increases, ε'' of S0-S3 also shows a decreasing trend, which indicates that the dielectric loss capability of the material decreases overall with the increase of NH2-PDA@NFO addition. In addition, S0-S3 showed multiple small fluctuation peaks in the mid-to-high frequency range (10-18 GHz), which is a manifestation of multiple polarization relaxation. Charge accumulation at heterogeneous interfaces such as GO and PAA interface, MXene and PAA interface, GO and NH2-PDA@NFO interface, MXene and NH2-PDA@NFO interface, GO and MXene interface, and GO and PAA interface will induce interfacial polarization relaxation and form loss peaks at specific frequencies.
[0057] In dielectric loss tangent (tanδ) ε ) Spectrum ( Figure 6 In part (c), the tanδ of S0-S3 ε Overall, they all decrease slowly with increasing frequency f. Specifically, the tanδ of S3... ε The dielectric efficiency is highest for S1, followed by S2, and then decreases for S1 and S0. This indicates that although ε' and ε'' decrease for NH2-PDA@NFO, the ratio of ε'' / ε' increases, resulting in higher dielectric loss efficiency. While S0 has a high ε'' value, its ε' value is also greater than ε'', leading to a higher tanδ. εThe low value indicates that its dielectric loss "efficiency" is not high, and it is more of a polarization energy storage than a loss. However, the ε' of S2 and S3 is adjusted to a more suitable range by NH2-PDA@NFO, while retaining sufficient ε'', which significantly improves the dielectric loss efficiency and is more conducive to achieving impedance matching.
[0058] exist Figure 6 In part (d), the μ' of S0-S3 generally shows a slow decreasing trend with increasing frequency f, with a more significant decrease in the 2-6 GHz band and a stabilization in the 6-18 GHz band. The μ' values of S0-S3 fluctuate between 0.98 and 1.12, but are generally close to 1. Specifically, the μ' value of S0 is almost stable at around 1 (0.98-1.0), indicating that S0 produces almost no magnetic response in the absence of NH2-PDA@NFO. The μ' of S1, S2, and S3 is significantly higher than 1 in the low-frequency band (2-6 GHz), which means that the introduction of NH2-PDA@NFO endows the material with magnetic response capability. At low frequencies, magnetic polarization (domain wall motion, magnetic moment orientation) contributes to the real part of the permeability. In the mid-to-high frequency range (6-18GHz), μ' of S0-S3 all approach 1, and the fluctuation decreases. This is because at high frequencies, the reversal of the magnetic moment cannot keep up with the changes in the alternating magnetic field, and the magnetic polarization response weakens, which is consistent with the Snoek limit effect of ferrite materials.
[0059] exist Figure 6 In part (e), μ'' of S0-S3 decreases significantly in the 2-6 GHz band and flattens out in the 6-18 GHz band. S2 and S3 show negative values in the 16-18 GHz band, which is a normal phenomenon caused by electromagnetic coupling. The μ'' of S1, S2, and S3 increases with the increase of NH2-PDA@NFO addition, indicating that NH2-PDA@NFO is the core source of magnetic loss. The small fluctuation peaks appearing in the mid-to-high frequency band correspond to the magnetic loss mechanisms such as natural resonance and exchange resonance of NH2-PDA@NFO, and these resonance peaks are important contributors to magnetic loss.
[0060] Magnetic loss tangent (tanδ) of S0-S3 μ () Figure 6 The trend of the (f) part with frequency f is consistent with the trend of μ''. With the increase of NH2-PDA@NFO content, the magnetic loss efficiency increases, therefore the tanδ of S0-S3... μ The values increase sequentially. Compare with tanδ. μ and tanδ ε It can be seen that: tanδ of S0-S3 ε Higher than tanδ μThis indicates that the loss of the sample to EMW is mainly dielectric loss, with magnetic loss as a secondary factor. The role of NH2-PDA@NFO is more about introducing magnetic loss and controlling the dielectric constant, thereby achieving synergy between dielectric and magnetic losses.
[0061] Depend on Figure 10 As shown in section (a), the order of ε′ values for the five materials is: S2 > NC / NFO-PDA / MX / rGO > C / NFO / MX / rGO > NC / NFO / MX > NC / NFO / rGO. Furthermore, the ε′ values of all five materials decrease with increasing f, exhibiting typical dielectric dispersion characteristics. Notably, all samples show weak oscillations in the high-frequency range (12-18 GHz), which can be attributed to the resonant response under the combined effects of interfacial polarization and dipole polarization.
[0062] S2 was modified in two steps using PDA and APTES to introduce a large number of amino groups onto the surface of NFO particles. These amino groups were then fixed to the PAA-derived NC matrix, MXene, and rGO sheets through chemical cross-linking, thereby constructing abundant NFO-carbon, MXene-rGO, and carbon matrix-MXene heterointerfaces. The abundance of heterointerfaces promoted charge accumulation and significantly enhanced the interfacial polarization effect, resulting in S2 exhibiting the highest ε′ value.
[0063] NC / NFO-PDA / MX / rGO, treated only with PDA, lacks the long-chain amino groups provided by APTES, resulting in reduced chemical cross-linking and weakened interfacial bonding. Its number of heterointerfaces is less than that of S2, hence its ε′ value is slightly lower than S2. In C / NFO / MX / rGO, the NFO is unmodified, making magnetic particles prone to aggregation, further reducing the number of heterointerfaces and lowering its ε′ value. NC / NFO / MX and NC / NFO / rGO, lacking rGO and MXene respectively, directly lose a type of carbon-based heterophase, significantly reducing the number of interfaces and thus continuously lowering the ε′ value. Among them, NC / NFO / rGO suffers the most severe heterointerface loss due to the lack of highly conductive MXene, hence its lowest ε′ value.
[0064] Depend on Figure 10As shown in section (b), the ε'' value of all samples decreases with increasing f, exhibiting significant fluctuations and oscillations in the 12-18 GHz range. This is mainly attributed to the dipole relaxation on the MXene and rGO sheets. Carbon material defects and N-doped sites, acting as dipole centers, undergo polarization relaxation at high frequencies, contributing additional dielectric losses. Numerically, the ε'' value of NC / NFO-PDA / MX / rGO is the highest, reaching 5.34 at 2.0 GHz; sample S2 is second. The ε'' values of C / NFO / MX / rGO and NC / NFO / MX decrease sequentially; while the ε'' value of NC / NFO / rGO is lower than that of the other samples, remaining within the 1-2 range throughout. MXene possesses excellent conductivity and is the main source of conductivity loss in the system. The removal of MXene from NC / NFO / rGO disrupts the integrity of the conductive network, restricts carrier migration, and significantly reduces conductivity loss, resulting in a corresponding significant decrease in its ε'' value. NC / NFO-PDA / MX / rGO is only modified with PDA, resulting in a low degree of chemical cross-linking. The NFO-carbon matrix interface is loosely bonded, with numerous interfaces primarily based on physical contact, leading to strong interfacial polarization losses, hence its highest ε'' value. However, excessively loose interfaces can also cause excessive losses, resulting in strong reflection of electromagnetic waves upon reaching the material surface, making it difficult for them to penetrate the material's interior.
[0065] In contrast, the introduction of APTES in S2 not only provides more cross-linking reaction sites, but its long-chain amino groups can also reduce the steric hindrance of the reaction and increase the degree of cross-linking. Thus, while maintaining sufficient heterogeneous interfaces to obtain considerable losses, it effectively avoids the loss overload caused by excessively loose interfaces.
[0066] like Figure 10 As shown in section (c), the tanδε of all samples initially increases and then decreases with increasing f, reaching a minimum in the 8-10 GHz range, and then continuously increases in the 10-18 GHz range. Among them, NC / NFO@PDA / MX / rGO and C / NFO / MX / rGO show the most significant increases in tanδε in the high-frequency band (14-18 GHz), with maximum values of 0.57 and 0.51, respectively. This indicates that their dielectric loss capability is too strong, which easily leads to severe impedance mismatch, causing most electromagnetic waves to be directly reflected at the material surface and difficult to penetrate the interior for effective dissipation. In contrast, the tanδε of S2 is stable in the 0.32-0.44 range with gentle fluctuations; its ε' and ε'' change synchronously, and the tanδε is within a reasonable range, which better balances loss capability and impedance matching. The lack of MXene in NC / NFO / rGO results in insufficient conductivity and low overall loss efficiency. Electromagnetic waves cannot be effectively converted into heat energy after entering the material. Therefore, its tanδε value is the lowest across the entire frequency band, remaining at 0.2-0.28.
[0067] like Figure 10 As shown in section (d), the μ' values of the five samples fluctuated slightly within the 2-14 GHz range. Among them, NC / NFO / MX and NC / NFO / rGO showed significant increases in the 14-18 GHz range, with maximum values of 1.20 and 1.12, respectively. This phenomenon may originate from the local aggregation of NFO particles in these two samples: strong magnetic dipole coupling exists between aggregated particles, inducing abnormal magnetic responses in the high-frequency region, leading to an anomalous increase in μ'. In contrast, the μ' values of S2 and C / NFO / MX / rGO remained stable around 0.98-1.10 throughout the entire test frequency band; while NC / NFO-PDA / MX / rGO, due to the weaker bonding between NFO and the carbon matrix interface, had magnetic particles isolated and shielded by the carbon layer, suppressing magnetic domain movement, resulting in a generally lower μ' level.
[0068] In the 2-6 GHz range, all samples showed obvious resonance peaks in their μ''-f curves. Figure 10 (e) This peak corresponds to the typical natural ferromagnetic resonance of nickel ferrite. As the frequency increases further, the μ'' value gradually decreases and is accompanied by small oscillations. C / NFO / MX / rGO shows a second significant loss peak in the 12-14 GHz range, which may be due to the aggregation of unmodified NFO particles. Some aggregates induce additional magnetic resonance, thus forming a secondary loss peak; however, aggregation leads to uneven distribution of magnetic particles, resulting in unstable loss performance. NC / NFO-PDA / MX / rGO has a low degree of chemical cross-linking with the carbon matrix. The NFO particles are physically encapsulated and isolated by the carbon matrix, making it difficult to effectively release magnetic loss, thus its overall μ'' is the lowest.
[0069] tanδμ-f( Figure 10The trend of the (f) part of the curve with frequency is basically consistent with that of μ''-f. In the 2-4 GHz frequency band, all samples show significant loss peaks; when the frequency increases further, tanδμ generally shows a decay trend, and the curve is accompanied by multiple resonance fluctuations. Comprehensive analysis of the above results shows that: the absence of either MXene or rGO will directly lead to a large loss of heterogeneous interface and conductive network, thus significantly reducing dielectric energy storage and dielectric loss; when NFO is not modified, the particles are prone to agglomeration, resulting in distortion of the magnetic permeability parameter; when only PDA is used for modification, due to the lack of amino chemical crosslinking sites introduced by APTES, the interfacial bonding between NFO and carbon matrix is weak, and magnetic loss is severely suppressed; the S2 sample uses two-step amino modification of PDA+APTES, and simultaneously introduces MXene and rGO dual carbon sources: on the one hand, it constructs a rich heterogeneous interface, achieving considerable dielectric energy storage and dielectric loss; on the other hand, the magnetic NFO particles are uniformly dispersed, and the magnetic loss is fully utilized. The synergistic effect of dielectric loss and magnetic loss, along with good impedance matching, results in S2 exhibiting optimal electromagnetic wave absorption performance.
[0070] Reflection loss (RL) directly reflects the material's absorption performance of electromagnetic waves and can be calculated using formulas (1) and (2): (1) (2) In the formula, Z in (Ω) represents the material input impedance; Z0 (Ω) represents the intrinsic impedance in free space; c represents the speed of light in vacuum; d (m) represents the thickness of the absorbing material coating.
[0071] Depend on Figure 7 From part (a), we can see that when S0 reaches 5.50 mm, RL min =-26.60dB, at which point EAB=1.12GHz. Since S0 contains only high-dielectric-constant GO / MXene and lacks magnetic response, impedance mismatch occurs, and most of the EMW is reflected by the aerogel surface. S0 relies solely on dielectric loss to absorb the EMW, resulting in a single loss mechanism. From the 2D contour plot ( Figure 7 As can be seen from part (b), the effective absorption of EMW by S0 covers the entire S-band, C-band, X-band and part of the Ku-band. When d=2.17mm, EAB reaches its maximum value of 3.72GHz.
[0072] The addition of NH2-PDA@NFO introduces magnetic loss into S1, reducing its dielectric constant and improving impedance matching. When d = 4.50 mm, RL... minThe voltage reached -39.08 dB, and the EAB was 2.21 GHz. This may be due to insufficient NH2-PDA@NFO content, resulting in low EAB and RL in S1. min Both are weaker than S2 and S3. Figure 7 In part (c), when d=2.0mm, the maximum EAB of S1 is 3.55GHz. The effective absorption of EMW by S1 can cover the entire S-band, C-band, X-band and Ku-band.
[0073] Compared to S3, S2 has a moderate amount of NH2-PDA@NFO added, its dielectric constant is tuned to the optimal range, and its impedance matching is optimal, making it easier for electromagnetic waves to penetrate the material. The RL of S2... min Both EAB and EAB have been improved and expanded. Figure 7 (e) portion). When d = 4.50 mm, RL min =-58.46dB. From the contour map of S2 ( Figure 7 As can be seen from part (f), S2's effective absorption of EMW covers the entire S-band, C-band, X-band, and Ku-band. Furthermore, when d = 3.50 mm, RL min Reaching -38.96dB, EAB=3.07GHz; when d=4.20mm, RL min Reaching -39.17dB, EAB=2.48GHz; when d=5.0mm, RL min The impedance reaches -44.51 dB, with an EAB of 1.98 GHz. When d is 2.13 mm, S2's EAB reaches its maximum value of 5.25 GHz. This may be because the excessive addition of NH2-PDA@NFO leads to an excessive reduction in dielectric constant, weakening conductivity and interface polarization losses, resulting in impedance mismatch in S3 and difficulty in efficient electromagnetic wave incidence. The overall synergistic effect of S3 is not as good as that of S2. The RL of S3... min =-47.51dB (d=4.50mm), at this time EAB is 2.53GHz ( Figure 7 (g) section). From the 2D contour map of S3 ( Figure 7 As can be seen from the (h) section, the RL attenuation depth of S3 is lower than that of S2, the strong absorption region shifts to a lower thickness, the coverage frequency band narrows, and the absorption in the high-frequency band weakens. When d is 2.04mm, the EAB of S3 reaches its maximum value of 5.07GHz.
[0074] The RL-f curve of S2 ( Figure 7 Similar to (e) part, the RL-f curve of NC / NFO-PDA / MX / rGO ( Figure 11In part (a), the absorption peak shifts towards lower frequencies as d increases. When d = 4.5 mm, the minimum reflection loss RLmin = -45.84 dB, corresponding to EAB = 2.21 GHz. Compared to S2, the absolute value of RLmin is significantly reduced, EAB is slightly narrowed, and the RL peak value at each matching thickness is generally smaller than that of S2. In the 2D contour plot of NC / NFO-PDA / MX / rGO ( Figure 11 In part (b), when d = 2.0 mm, the EAB can reach 3.79 GHz. Figure 10 As can be seen from the (af) part, although ε'' of NC / NFO-PDA / MX / rGO is at a relatively high level, its tanδ μ The impedance is significantly suppressed. Excessive dielectric loss and insufficient magnetic loss lead to an imbalance in dielectric / magnetic loss and a deterioration in impedance matching. Although the material has strong dielectric loss capability, a large amount of electromagnetic waves are reflected at the surface and cannot effectively dissipate into the interior.
[0075] In the C / NFO / MX / rGO system, the dual-carbon composition of MXene and rGO imparts high dielectric loss; however, the aggregation of NFO particles disrupts the dielectric / magnetic synergy, making it difficult to fully utilize magnetic loss and further degrading the absorption performance. Compared with NC / NFOPDA / MX / rGO, the RL of C / NFO / MX / rGO is further reduced ( Figure 11 (c) of the diagram: When RLmin reaches -40.23 dB, EAB is 2.09 GHz. (Based on 2D contour maps) Figure 11 As can be seen from the (d) part, when the matching thickness d=2.0mm, the EAB can reach 5.82GHz.
[0076] For the NC / NFO / MX system, when d=5.5mm, RLmin is -35.44dB, corresponding to EAB of 1.82GHz. Figure 11 (e)); It is worth noting that when d=2.2mm, although RLmin is only -32.86dB, EAB is as high as 6.11GHz ( Figure 11 (f) After removing rGO, only the MXene component remains in the NC / NFO / MX system. rGO can construct a continuous sheet-like conductive network and provide a large number of interface defects and dipole polarization sites; after removing rGO, the integrity of the conductive network decreases and the number of heterointerfaces is significantly reduced. Therefore, although NC / NFO / MX can obtain a wide absorption bandwidth, its absorption depth is insufficient; to obtain a higher absorption intensity, the material thickness needs to be increased, which is not conducive to the lightweight application of the material. Overall, the absorption performance of NC / NFO / MX for EMW is significantly worse than that of S2.
[0077] Within the tested thickness range, the RLmin of NC / NFO / rGO was only 20.73 dB. Figure 11 The (g) portion was significantly weaker than other samples; and its RL was greater than 10 dB for most thicknesses. When d = 2.4 mm, the EAB reached a maximum of 3.95 GHz. Figure 11 (h part). MXene has high intrinsic conductivity and is the main source of conductivity loss in the system. After removing MXene, the conductivity of the system decreases significantly. ε′), ε″, and tanδε are all significantly reduced throughout the entire test frequency band. At the same time, due to the absence of MXene sheets, the system loses a large number of MXene-rGO and MXene-NFO heterojunctions, resulting in a severe weakening of interface polarization and conductivity loss. Relying solely on rGO and NFO, the overall dielectric loss is severely insufficient; after EMW enters the material, there is a lack of sufficient loss mechanism to convert electromagnetic energy into heat energy, and a large amount of electromagnetic waves are directly transmitted out, ultimately resulting in poor absorption performance.
[0078] The attenuation coefficient (α) characterizes the material's ability to attenuate EMW losses and can be calculated using formula (3). The larger α is, the stronger the material's ability to attenuate EMW losses.
[0079] (3) Figure 8 Part (a) shows the variation of α with frequency f. α increases with increasing f for all S0-S3, with a significant increase in the high-frequency range (12-18 GHz). This aligns with the physical law that under high-frequency conditions, alternating electromagnetic fields accelerate carrier migration, polarization reversal, and magnetic moment resonance, thereby amplifying losses. Furthermore, the multiple continuous fluctuations in the four curves are caused by the superposition of multiple polarizations and magnetic resonance relaxation. On the other hand, in the 2-18 GHz range, α exhibits a variation pattern of S3 > S2 > S1 > S0. S0 relies solely on the conductivity loss of GO / MXene and has no source of magnetic loss, thus exhibiting the weakest attenuation across the entire frequency band. With the introduction of NH2-PDA@NFO, its natural resonance / exchange resonance magnetic loss constructs a GO-MXene-NH2-PDA@NFO-PAA heterojunction interface in S1-S3, enhancing interface polarization loss and improving the attenuation capability of electromagnetic waves through dual-loss channels.
[0080] Figure 8 Part (b) shows the trend of the eddy current loss coefficient (C0) as a function of frequency f. The eddy current coefficient can be calculated according to formulas (4) and (5): (4) (5) In the formula, C0 is the eddy current coefficient; σ (S / cm) is the electrical conductivity; and μ0 (H / m) is the vacuum conductivity.
[0081] If eddy current loss is the sole source of magnetic loss, C0 will not change with increasing f; if C0 decreases with increasing f, it indicates that magnetic loss is dominated by natural resonance and exchange resonance. Since S0 has no magnetic component, it has almost no magnetic loss, and C0 approaches 0. In the 2-18 GHz range, the C0 of S1-S3 decreases rapidly and significantly in the low-frequency range (2-8 GHz), changes more slowly in the mid-to-high-frequency range (8-14 GHz), and approaches 0 in the 14-18 GHz range. These results indicate that the magnetic loss of S1-S3 is the result of the combined effects of natural resonance, exchange resonance, and eddy current loss.
[0082] Z in / Z0 is used to evaluate the impedance matching degree between the material and free space, and can be calculated by formula (6):
[0083] When Z in / Z0~f curve ( Figure 8 (c) The closer the value is to 1, the easier it is for electromagnetic waves to penetrate the material. As the amount of NH2-PDA@NFO added increases from 0 mg to 100 mg (S0-S2), the excellent impedance matching frequency band of the composite aerogel continues to widen, and the matching peak value gradually approaches the ideal value of 1. When the amount added is further increased to 150 mg (S3), the excessive magnetic phase excessively reduces the dielectric constant of the system, the impedance matching window shrinks, and the matching effect decreases. The S2 sample has a matching peak value of 1.05 and has the widest excellent matching range. The dielectric constant and permeability achieve the optimal balance, providing a basis for efficient electromagnetic wave incidence. Combined with the synergistic loss of the dielectric-magnetic dual channels, it ultimately exhibits the best electromagnetic wave absorption performance. The S0 sample without nickel ferrite only achieves matching in an extremely narrow low-frequency range, with severe impedance mismatch across the entire frequency band and the worst absorption performance.
[0084] Depend on Figure 13 As shown in section (a), the C0 values of NC / NFOPDA / MX / rGO, C / NFO / MX / rGO, NC / NFO / MX, and NC / NFO / rGO are relatively high in the 2-10 GHz range, and generally show a rapid decreasing trend with increasing f. In the 10-16 GHz range, C0 drops to a lower level with slight oscillations, while in the high-frequency range of 16-18 GHz, C0 hardly changes with frequency. These results indicate that the magnetic loss of these five systems is not dominated by eddy current loss, and the natural resonance and exchange resonance of the NFO are also involved.
[0085] Impedance matching curves of all samples ( Figure 13The trends in (b) are generally consistent: a rapid increase in the 2-5 GHz range, reaching a peak near 4-5 GHz, with some samples exceeding 1.0; followed by a rapid decrease in the 5-12 GHz range, and a slow rebound in the 12-18 GHz range. The purple dashed line in the figure indicates the optimal impedance matching position corresponding to |Zin / Z0|=1. For NC / NFO / rGO, due to its overall low dielectric constant, the impedance value is relatively large, and its |Zin / Z0| peak value is much greater than 1. Although its impedance in the low-frequency range seems good, there is a serious mismatch in the high-frequency range; at the same time, the attenuation coefficient α of this system is low, and even with EMW incident, its loss capability is still weak, thus the corresponding RL performance is poor. The excessively high ε″ of NC / NFOPDA / MX / rGO results in excessive dielectric loss, causing its impedance to deviate significantly from 1. This leads to a large amount of electromagnetic waves being directly reflected from the material surface, thus limiting its absorption performance. The S2 system, through a two-step modification using PDA and APTES, effectively balances the dielectric and magnetic parameters, achieving a |Zin / Z0| peak value close to 1. This results in better impedance matching over a wider frequency band, allowing more electromagnetic waves to penetrate the material and laying the foundation for excellent RL performance.
[0086] Depend on Figure 13 As shown in section (c), C / NFO / MX / rGO has the highest α value, exceeding 258 at f=17GHz; NC / NFOPDA / MX / rGO is second; S2 ranks third, with a maximum α value of approximately 198; the α value of NC / NFO / MX is significantly lower than the first three groups, while NC / NFO / rGO has the lowest across the entire frequency band. The highest α value of C / NFO / MX / rGO indicates its strong ability to dissipate electromagnetic waves (EMWs); however, its |Zin / Z0| deviates from 1, indicating poor impedance matching, with most electromagnetic waves reflected at the material surface, thus its resistance-to-electrical (RL) performance is weaker than S2. S2 maintains a high α value and possesses optimal impedance matching, achieving a synergistic balance between impedance matching and attenuation capability: EMWs can be incident in large quantities into the material and efficiently dissipated internally, ultimately achieving optimal RL performance. For the NC / NFO / rGO system lacking MXene, its dielectric loss is severely insufficient, and even with EMW incident, it cannot effectively dissipate electromagnetic energy.
[0087] The influence of conductivity loss and dielectric loss on microwave absorption performance is analyzed based on Debye relaxation theory: (7) In the formula, ε s Represents the static dielectric constant, ε ∞ It represents the high-frequency dielectric constant.
[0088] From formula (7), it can be seen that a single relaxation corresponds to a single standard semicircle, multiple semicircles represent multipolar relaxation, and the curve tail represents the contribution of conductivity loss. Figure 8 As shown in section (d), S0-S3 all exhibit a multi-segment incomplete semicircle morphology with a linear tail at the end. The segmented semicircles in S0-S3 confirm the existence of multiple interfacial polarization relaxations in the system, originating from multiple heterogeneous interfaces within the aerogel. At these interfaces, charge accumulation undergoes dipole relaxation under the influence of an alternating electric field, which is a significant source of dielectric loss. The four curves tail upwards on the right, with the linear tail dominated by the conductivity loss of MXene / GO, indicating that conductivity loss is an indispensable component of the dielectric loss of this material. With the increase of NH2-PDA@NFO addition, the free carrier concentration decreases, the macroscopic ε' decreases, and the Cole-Cole semicircle curve shifts to the left overall. Simultaneously, NH2-PDA@NFO introduces more heterogeneous interfaces, increasing the number of semicircle segments and the number of polarization relaxation loss sites, which further explains the experimental results of higher dielectric loss tangents in S2 and S3.
[0089] Cole-Cole curves of NC / NFO-PDA / MX / rGO ( Figure 12 Part (a) shows multiple distorted incomplete semicircular arcs, and the high-frequency ε'' increases sharply with the increase of ε', indicating that multiple dielectric relaxations and strong conductivity losses coexist in this sample. Although PDA-derived carbon introduces abundant polar sites and heterogeneous interfaces, its high conductivity also easily causes impedance mismatch. Figure 12 In part (b), a clear distorted semicircular arc can be observed, and the conductivity loss in the high-frequency region is also significant, achieving relaxation-conductivity synergistic loss; however, due to the lack of a special interface constructed by amino modification, the number of polarization sites and interface types of C / NFO / MX / rGO are still relatively limited. The Cole-Cole curve of NC / NFO / MX ( Figure 12 The (c) part is approximately a monotonically rising sloping straight line with almost no obvious Cole-Cole arc, indicating that its loss mechanism is dominated by electrical conduction loss, the interface relaxation polarization process is insufficient, and the loss source is relatively simple. Figure 12 In part (d), a series of distorted small circular arcs with small radii appear, and the upward amplitude at the tail of the curve is weak, confirming that NC / NFO / rGO can generate a certain degree of dielectric relaxation polarization; however, due to the lack of MXene highly conductive sheets, the conductivity of the conductive network is poor, and the contribution of conductivity loss is insufficient.
[0090] Compared to the four control samples mentioned above, the Cole-Cole curve of S2 ( Figure 8The (d) portion exhibits numerous semi-circular arcs with moderate distortion, and the tail shows only a moderate increase in conductivity. The introduction of amino-modified NH2@NFO constructs more NFO-carbon-MXene-rGO multi-element heterogeneous interfaces, inducing abundant interfacial space charge polarization; simultaneously, defects in pyrolytic carbon provide numerous dipole polarization centers, thus generating sufficient dielectric relaxation effect. MXene and rGO interlock to form a continuous but not overly conductive conductive network, limiting conductivity loss to a reasonable range, thereby avoiding problems such as excessively high conductivity in NC / NFO-PDA / MX / rGO, NC / NFO / MX relying solely on conductivity loss, and insufficient conductivity in NC / NFO / rGO. Comparison with four control samples confirms that S2 achieves the optimal synergistic balance between multiple dielectric relaxation polarizations and conductivity loss: ensuring both the dielectric loss capability of electromagnetic waves and avoiding impedance mismatch caused by overconductivity. This balance is one of the key dielectric mechanisms that give S2 its excellent microwave absorption performance.
[0091] The absorption mechanism of electromagnetic waves (EMWs) in the quaternary composite aerogel NC / NFO / MX / rGO can be attributed to multiple synergistic processes. First, during aerogel formation, the sublimation of ice crystals generates a porous structure with a rich pore size distribution. This structure not only facilitates EMW ingress into the material, thereby reducing interfacial reflection and improving impedance matching, but also provides numerous internal interfaces that promote multiple reflections and scattering of EMWs. Secondly, the uniformly dispersed MXene and GO within the composite material construct a continuous conductive network. In this network, the migration of free electrons effectively converts electromagnetic energy into Joule heat, thus efficiently dissipating wave energy. Furthermore, the integration of multiple components within the composite material creates a rich variety of heterogeneous interfaces, which is crucial for enhancing dielectric loss. Specifically, a core-shell interface exists between the NC / NFO within NC / NFO / MX / rGO and its shell-derived amorphous carbon cage, while a contact interface exists between NC / NFO and the interwoven MXene / GO. Under an alternating electromagnetic field, migrating electrons are effectively captured and accumulated at these boundaries. This strong charge accumulation induces a powerful space charge polarization effect (interfacial polarization), converting electromagnetic energy into thermal energy. The inherent defects, vacancies, and doped nitrogen and other heteroatoms within NC / NFO and MXene / GO further act as local polarization centers, inducing a significant dipole relaxation process that continuously consumes microwave energy. Doping of nitrogen and other heteroatoms in NC / NFO and MXene / GO further enhances this process, allowing dipole relaxation to more effectively and continuously consume microwave energy. Finally, the ferromagnetism of the NC / NFO particles contributes to the key magnetic loss mechanism. On one hand, their magnetic anisotropy produces natural resonance; on the other hand, the alternating magnetic field induces eddy currents within the magnetic particles, leading to eddy current losses. These mechanisms work synergistically to improve the overall electromagnetic wave attenuation capability of the composite material. In summary, the possible EMW absorption mechanisms of NC / NFO / MX / rGO are as follows: Figure 9 As shown.
[0092] The adsorption performance of product S2 on methylene blue (MB) was tested, and the results are as follows: Figures 14-17 As shown.
[0093] Batch adsorption experiments were conducted to investigate the effects of pH, adsorbent dosage, and initial MB concentration (ρ0) on the adsorption performance of S2. Each condition was measured in triplicate, and the average value was taken. The specific experimental procedure was as follows: A certain amount of S2 was added to a 100 mL Erlenmeyer flask, then mixed with 50 mL of MB solution of a specified concentration. The mixture was then placed in a constant-temperature shaker and shaken at 100 rpm / min for a certain period of time. After adsorption, the adsorbent was separated by applying an external magnetic field. The absorbance of the solution was measured at the maximum absorption wavelength of MB (665 nm) using a UV-Vis spectrophotometer to determine the equilibrium concentration of the dye (ρ0). eThe pH of the MB (50 mL, 100 mg / L) solution was adjusted to the range of 2.0-10.0 using 0.1 mol / L HCl or NaOH solution, and the effect of pH on the adsorption performance of S2 was investigated.
[0094] In the adsorption kinetics experiment, 0.14 g of S2 was accurately weighed and added to 100 mL of MB solutions with different initial concentrations (100, 200, 300, and 400 mg / L). The pH was set to 7.0. Under constant oscillation conditions, the absorbance of the samples was collected at predetermined time intervals to determine the instantaneous concentration of the dye (ρ). t ).
[0095] Adsorption isotherms were conducted at different temperatures (283.15, 293.15, 303.15, and 313.15 K), with initial MB solution concentrations ranging from 50 to 500 mg / L. Each flask was shaken in a constant-temperature shaker for 3 hours to ensure the adsorption process reached equilibrium. The equilibrium adsorption capacity (Q) was determined. e (mg / g), instantaneous adsorption capacity at time t (Q) t The removal rate (η) and the removal concentration (mg / g) are calculated using the following formula:
[0096] In the formula, ρ0 (mg / L), ρ t (mg / L), and ρ e (mg / L) represent the initial concentration, instantaneous concentration, and equilibrium concentration of the dye solution, respectively; V (L) is the volume of the dye solution; and m (g) is the mass of the adsorbent.
[0097] Desorption and reusability of S2: 0.14 g of S2 was added to 200 mL of 100 mg / L MB aqueous solution. After shaking at 100 rpm / min for 3 h at 303.15 K, the concentration of MB in the supernatant was measured. S2 adsorbed with MB (denoted as MB-S2) was collected using magnetic separation technology, and then immersed in 0.1 mol / L HCl solution and shaken at 300 rpm / min for 2 h to achieve desorption. Finally, the adsorbent was separated and washed with deionized water so that it could be used for the next adsorption experiment. Following this procedure, a total of six adsorption-desorption cycles were carried out, and η was calculated according to formula (10).
[0098] Depend on Figure 14 As can be seen in part (a), under different adsorption temperatures of 283.15 K, 293.15 K, 303.15 K, and 313.15 K, Q increases with the increase of ρ0 of MB. eThe concentration initially rises rapidly, then gradually slows down, eventually approaching saturation. In the low-concentration region, a significant concentration difference exists between MB molecules and the S2 surface, resulting in strong mass transfer. Simultaneously, the S2 surface is rich in active sites, hence Q... e Rapid growth; however, at high concentrations, the effective adsorption sites on the S2 surface are gradually filled by MB molecules, and the adsorption process approaches saturation. e The growth rate of Q decreased significantly. Furthermore, under the same ρ0 condition, Q... e The increase with increasing temperature indicates that the adsorption process is endothermic. As the temperature rises, the thermal motion of MB molecules intensifies, which increases the diffusion rate of dye molecules into the S2 channel and strengthens the π-π stacking, electrostatic, and hydrogen bonding interactions between the oxygen-containing functional groups in PAA, MXene, GO, and NC / NFO and the dye.
[0099] Figure 14 Part (b) presents the values of Q when ρ0 is 100 mg / L, 200 mg / L, 300 mg / L, and 400 mg / L. t The graph shows the change in Q over adsorption time. As can be seen from the graph, under these four different concentration conditions, Q... t All showed characteristics of rapid adsorption in the early stage, slow stabilization in the middle and later stages, and finally reaching adsorption equilibrium. Specifically, the rapid adsorption stage occurred from 0 to 60 min, during which numerous exposed active sites on the S2 surface rapidly captured MB in the liquid phase, resulting in a high adsorption rate. From 60 to 140 min, a slow adsorption stage emerged, with the S2 surface sites gradually becoming saturated. Dye molecules needed to slowly diffuse into the internal structure of S2, and internal diffusion became the controlling step in the adsorption rate. When t > 140 min, the curve essentially stabilized, and adsorption reached a dynamic equilibrium. Moreover, at the same adsorption time, the higher the ρ0, the higher the Q... e The higher the concentration, the greater the liquid-solid concentration gradient, which enhances the mass transfer driving force, allowing a unit of adsorbent to bind more dye molecules.
[0100] Figure 14 Part (c) represents the effect of solution pH on Q. e The effect of pH increasing from 2 to 7. e The concentration increased from 16.47 mg / g to 69.33 mg / g; subsequently, when the pH was further increased to 10, Q... e It decreased to 12.33 mg / g. This is because MB is a cationic dye, and in an acidic environment, the large amount of H+ in the solution... + Competition with MB for negatively charged adsorption sites on the S2 surface leads to Q e Lower. In addition, a large amount of H... +This causes the S2 surface to become protonated and positively charged, and the resulting electrostatic repulsion further inhibits dye adsorption. As pH increases, H... + As the concentration decreases, the amino, carboxyl, and hydroxyl groups on the S2 surface deprotonate, while the carboxyl / hydroxyl groups of graphene dissociate and become negatively charged. This enhances the electrostatic attraction between graphene and MB, increasing the activity of the adsorption sites and thus Q. e It continues to increase. However, as pH continues to rise, Q... e A rapid decrease. This could be due to excessively high concentrations of OH. - This alters the charge environment on the S2 surface, even causing the hydroxyl groups on the NC / NFO / MX / rGO surface to aggregate, and the pores in S2 to curl or even collapse, ultimately leading to a significant decrease in adsorption performance.
[0101] Figure 14 The (d) part is the ratio of S2 feed rate to Q. e The effect of η. Increasing the feed amount increases the total number of adsorption sites on the adsorbent, thus enabling the capture of more MB. As the S2 feed amount increases from 0.4 g / L to 2.0 g / L, η first rises rapidly from 15.92% to 97.02% (corresponding to a feed amount of 1.4 g / L), then slowly increases to 100% (corresponding to a feed amount of 1.8 g / L). Further increasing the feed amount does not significantly improve the removal efficiency. Q e The concentration of Q increases slightly within the range of 0.4-1.0 g / L, reaching a peak of 71.4 mg / g at a feed concentration of 1.2 g / L. When the feed concentration exceeds 1.2 g / L, Q... e It continued to decrease to 49.3 mg / g. Q e The trend of η changing with feed amount is opposite to that of Q. This may be because when the amount of adsorbent is insufficient, a unit of aerogel can fully utilize all adsorption sites, so Q... e The adsorption capacity is relatively high; however, when the amount of adsorbent increases, although the number of adsorption sites increases, the total amount of MB in the system is limited, resulting in a large number of adsorption sites remaining idle and the adsorption capacity being diluted, leading to a decrease in Q. e The dosage was gradually reduced. Considering both the economics and efficiency of the adsorbent, a dosage of 1.4 g / L was selected.
[0102] Adsorption isotherms can reveal the interaction between the adsorbent and the adsorbate, as well as Q. e With ρ e The relationship between them. Figure 15 In part (a), it can be observed that under four different temperature conditions (273.15 K, 283.15 K, 293.15 K, and 303.15 K), as ρ... e The increase of Q e It exhibits a trend of rapid increase at low concentrations and gradual leveling off at high concentrations. This phenomenon may be due to the change in ρ...e At lower concentrations, a large concentration gradient exists between the MB solution and the S2 surface, resulting in strong mass transfer driving forces. The abundant active sites on the S2 surface allow for rapid binding of MB cations; while at lower concentrations... e In higher stages, adsorption sites are gradually occupied by MB, and the adsorption rate slows down and approaches saturation. Furthermore, at the same ρ... e Under the condition, Q e The increase with increasing temperature confirms that the adsorption process is endothermic. To further investigate the adsorption characteristics, the adsorption equilibrium data at four temperatures were analyzed using the Langmuir (Equation 11) and Freundlich (Equation 12) models.
[0103]
[0104] Among them, Q max (mg / g) represents the maximum adsorption capacity, K L (L / mg) is the Langmuir constant related to the affinity of the binding site, K F (mg / g) and 1 / n are Freundlich constants, corresponding to adsorption capacity and adsorption strength, respectively; from Figure 15 As can be seen from parts (a) and (b) and the relevant data in Table 1, the equilibrium data fits the Langmuir model better than the Freundlich model, because the correlation coefficient (R²) is higher at the four different temperatures. 2 The values of 0.9962, 0.9937, 0.9883, and 0.9813 were all the highest. Furthermore, the adsorption capacity (Q) calculated by the Langmuir model was the highest. m.cal The adsorption values (163.6, 179.7, 206.5, and 229.1 mg / g) and the experimentally measured adsorption capacity (Q) m.exp The values (158.1, 176.2, 202.6 and 224.9 mg / g) are similar, indicating that monolayer adsorption plays a dominant role in the adsorption process.
[0105] Table 1. Relevant parameters of the adsorption isotherm model
[0106] Because the adsorption temperature affects the diffusion rate of the adsorbate molecules and Q... e It has an impact, therefore it plays a crucial role in the adsorption process. For example... Figure 15 As shown in part (a), with the same ρ0, Q increases with increasing temperature. eThe corresponding increase indicates that the adsorption of MB on S2 is an endothermic process. To further evaluate and understand this adsorption process, various thermodynamic parameters were measured, such as the Gibbs free energy change (ΔG0, kJ / mol), enthalpy change (ΔH0, kJ / mol), and entropy change (ΔS0, J / mol / K), which typically provide relevant information about the intrinsic energy changes involved in the adsorption reaction. The equilibrium constant k... d The calculation can be performed according to formula (13), while the thermodynamic parameters can be calculated using formulas (14) and (15), as shown below: (13) (14) (15) In the formula, k d (L / g) is the equilibrium constant, R represents the gas constant 8.314 (J / mol / K), and T (K) is the absolute temperature. According to Lnk... d The results of the linear relationship with 1 / T are shown in Table 2.
[0107] Thermodynamic analysis showed that a positive ΔH0 value indicates that the adsorption of MB by S2 is endothermic. Under four different temperature conditions, ΔG0 was negative, indicating that this adsorption process can proceed spontaneously. Further observation revealed that the absolute value of ΔG0 gradually decreased with increasing temperature, meaning that the spontaneous driving force of the adsorption process was continuously weakening. During adsorption, ΔS0 > 0, mainly due to the large amount of water molecules originally bound within the S2 pores being displaced into the solution during MB ion adsorption, leading to increased disorder in the entire system. Considering the changes in ΔH0, ΔS0, and ΔG, it can be clearly concluded that this adsorption process is mainly dominated by chemisorption, and that a high-temperature environment is more favorable for MB removal.
[0108] Table 2 Thermodynamic Relevant Parameters Adsorption kinetics is an important parameter for predicting the rate-controlling steps and mechanisms of adsorption processes. Therefore, a pseudo-first-order kinetic model (Equation (16)) and a pseudo-second-order kinetic model (Equation (17)) are used to analyze adsorption data: (16) (17) In the above equation, k1 (1 / min) and k2 (g / (mg·min)) are pseudo-first-order and pseudo-second-order rate constants, respectively.
[0109] The calculated adsorption kinetic parameters are summarized in Table 3. The results show that the kinetic parameters of S2 best fit the pseudo-second-order model. Its R... 2 The values were 0.9916, 0.9904, 0.9907, and 0.9877, respectively, all higher than the corresponding values of the pseudo-first-order model (0.9585, 0.9358, 0.9567, and 0.9677). Furthermore, the equilibrium adsorption capacity (Q) calculated by the pseudo-second-order model... e,cal (133.2 mg / g, 187.2 mg / g, 202.9 mg / g and 222.4 mg / g), which are closer to the experimentally measured Q than the pseudo-first-order model. e,exp The values were 129.9 mg / g, 181.8 mg / g, 206.9 mg / g, and 224.8 mg / g. Therefore, the pseudo-second-order kinetic model can explain the behavior of MB adsorption on S2. These results indicate that MB adsorption on S2 is mainly dominated by chemisorption, which may be attributed to electron exchange or sharing between the dye cationic groups and the negatively charged surface of the adsorbent.
[0110] Table 3. Relevant parameters of the dynamic model Besides high adsorption capacity, a promising adsorbent should also possess good reusability to meet the practical requirement of low cost. Adsorption-desorption experiments were conducted by eluting a dye-loaded adsorbent (MB-S2) with HCl solution (0.1 mol / L), followed by washing with deionized water, and then repeating the cycle. The regeneration and reuse performance of S2 was investigated in this process, and the results are as follows: Figure 15 As shown in section (f), the figure clearly shows that after six adsorption-desorption cycles, η still exceeds 80%, which fully demonstrates that S2 has good reusability. In conclusion, S2 can be used as a stable, low-cost, and efficient MB removal adsorbent.
[0111] To further investigate the interaction between MB and S2, we performed XPS and IR analyses on MB-S2 and compared the results with those of S2. Figure 16 As shown in part (a), sp in S2 2The π-π stacking of aromatic carbon and MB benzene ring delocalizes conjugated electrons, causing the binding energy to shift to a lower field. However, the positive charge of MB induces electron-withdrawing polarization in the carbon skeleton, reducing the electron cloud density of C=C carbon atoms and causing a shift in the peak field. Since the cation field polarization effect is slightly stronger than the π electron enrichment effect in the system, the C=C peak shifts from 284.7 eV to 284.9 eV after adsorption. The hydroxyl groups and O atoms in the ether bonds of N / C@NFO, PAA, and MXene / rGO contain lone pairs of electrons. These bind to MB cations through hydrogen bonds and electrostatic attraction, causing the O atom electron cloud to transfer to the MB molecule, indirectly reducing the electron shielding effect of the connected carbon atoms. The binding effect of the carbon nucleus on the inner 1s orbital is enhanced, increasing the binding energy, and the CO bond shifts from 285.6 eV to 286.1 eV. The nitrogen doping in N / C@NFO and PAA is responsible for adsorbing MB. + The core active site of the N atom undergoes a significant transfer of lone pair electrons to the cationic dye, resulting in a substantial decrease in the electron density of the carbon atom in the CN bond and a weakening of the shielding effect. The CN bond shifts from 286.7 eV to 287.3 eV. The binding energy of OC=O in S2 shifts from 289.5 eV before adsorption to 288.9 eV at a lower field. Residual COO on the PAA surface... - with MB + Electrostatic interactions occur, which push the carbonyl carbon to shift to a higher field. However, MB is a highly conjugated aromatic system. The surface coating of MB brings a delocalized electron-rich environment. π electrons continuously supply electrons to the carbonyl carbon through spatial polarization, which greatly increases the electron cloud density of the outer shell of carbon, enhances the 1s orbital shielding, and reduces the binding energy. The global π electron enrichment polarization effect is stronger than the local electron loss effect of oxygen atoms, and finally the OC=O characteristic peak shifts to a lower field.
[0112] In the O1s fine spectrum of MB-S2 ( Figure 16 In part (b), due to MB + Coordination with the N / C@NFO metal center disrupts part of the MO structure, reducing the peak intensity at 529.7 eV. The broken metal sites hydrate to form M-OH, thus significantly increasing the content of the M-OH component corresponding to the original 530.5 eV. Oxygen atoms in M-OH, C=O, and OCO are directed towards MB through hydrogen bonding and electrostatic interactions. + The supply of lone-pair electrons reduces the electron cloud density of the O atom, causing the corresponding characteristic peaks to shift towards higher binding energies to 531.3 eV, 532.1 eV, and 532.8 eV, respectively. Furthermore, the characteristic peak of adsorbed water shifts from 533.8 eV to a higher field to 534.08 eV. This is likely due to the large amount of MB... +The accumulation of water molecules on the S2 surface creates a localized positive electric field, and the residual water molecules in the polarization interlayer cause the electron clouds of oxygen atoms in the water molecules to shift towards the dye, reducing the electron density of O atoms. On the other hand, during the adsorption process, free water molecules are replaced and removed by the dye, leaving only bound water that forms multiple strong hydrogen bonds with the oxygen-containing functional groups of the matrix and methylene blue molecules. The hydrogen bonding further consumes the lone pair electrons of oxygen atoms. The two effects together cause the characteristic peak height field shift of adsorbed water.
[0113] N 1s fine spectrum ( Figure 16 Part (c) is fitted with five different types of nitrogen. The graphite nitrogen exposure sites embedded in the carbon framework are limited and only weakly polarized by the surface cation electric field, resulting in only a small high-field shift of 401.8 eV. At the same time, methylene blue quaternary ammonium (-N) appears in the 402.7 eV range. + (CH3)2) The newly formed characteristic peaks directly demonstrate that methylene blue is fixed on the aerogel surface, clarifying that doped nitrogen and metal coordination sites cooperate in the adsorption process.
[0114] In the IR spectrum of MB-S2 ( Figure 16 In part (d), COO - Antisymmetric vibration from 1593cm -1 Blue shifted to 1609cm -1 COO - Symmetrical stretching from 1466cm -1 Redshifted to 1443cm -1 This may be due to COO - Electrostatic forces and intermolecular hydrogen bonding between the molecule and MB; 1519 cm -1 The peaks are characteristic vibrational peaks of the MB benzene ring, indicating that S2 undergoes π-π stacking interactions with the dye. The defect peak of S2 is located at 1356 cm⁻¹. -1 Offset to 1365cm -1 CO slightly blue shifted to 1118cm -1 The Si-O-Si redshifts to 1036 cm⁻¹ due to hydrogen bonding. -1 1188cm -1 1003cm -1 This is a novel characteristic absorption of nitrogen-containing heterocyclic molecules in MB. The fingerprint region is 947-699 cm⁻¹. -1 A series of out-of-plane bending characteristic peaks of the MB aromatic ring CH were observed. Infrared results indicate that the adsorption mechanism of S2 on MB can be attributed to multiple concerted processes ( Figure 17 Firstly, S2 has numerous active sites on its surface and within its interior, which can effectively adsorb MB and facilitate its entry into the composite material structure. The superior adsorption performance of S2 primarily stems from the -COO groups on its surface. -The electrostatic interaction between S2 and MB, the π-π conjugation between the numerous benzene rings in S2 and MB, and the hydrogen bonding between -OH, -NH2, CO, Si-O-Si in S2 and MB.
Claims
1. A method for preparing a multi-level heterogeneous composite aerogel, characterized in that, The steps are as follows: S1: Nickel ferrite was subjected to dopamine polymerization and amination modification in sequence to obtain amination-modified polydopamine-coated nickel ferrite particles. S2: Polymerize 2,2-bis[4-(4-aminophenoxy)phenyl]propane with 3,3′,4,4′-biphenyltetracarboxylic dianhydride in N,N-dimethylformamide, and obtain polyamic acid by washing and drying; S3: Polyamic acid and triethylamine are mixed in water to obtain a polyamic acid salt solution; graphene oxide, monolayer MXene, polyvinylpyrrolidone and the amino-modified polydopamine-coated nickel ferrite particles are dispersed in water to obtain a dispersion; the polyamic acid salt solution and the dispersion are mixed and a crosslinking agent is added to obtain a composite precursor solution, which is then subjected to vacuum freeze-drying and pyrolysis under an inert atmosphere to obtain a multi-level heterostructure composite aerogel.
2. The method for preparing multi-level heterogeneous composite aerogel according to claim 1, characterized in that, The preparation method of nickel ferrite is as follows: ferric nitrate nonahydrate, nickel nitrate hexahydrate and ethylene glycol are dispersed in water, and sodium acetate and polyvinylpyrrolidone are added to react. After the reaction, the mixture is washed and dried to obtain nickel ferrite. The mass ratio of ferric nitrate nonahydrate, nickel nitrate hexahydrate, sodium acetate, and polyvinylpyrrolidone is 1.0-2.3:0.35-0.80:2.2-4.6:1; The reaction conditions are a temperature of 160-200℃ and a time of 12-24h.
3. The method for preparing multi-level heterogeneous composite aerogel according to claim 1, characterized in that, The steps of dopamine polymerization are as follows: nickel ferrite is dispersed in water, then Tris buffer and dopamine hydrochloride are added, and after reaction in the dark, it is washed and dried to obtain polydopamine-coated nickel ferrite. The mass ratio of nickel ferrite to dopamine hydrochloride is 3.75-6.25:1; The conditions for the light-protected reaction are a temperature of 25-30℃ and a time of 12-36 hours.
4. The method for preparing multi-level heterogeneous composite aerogel according to claim 1, characterized in that, The steps of the amination modification method are as follows: the nickel ferrite treated with dopamine polymerization is dispersed in anhydrous ethanol, and then 3-aminopropyltriethoxysilane is added and heated to reflux reaction. After the reaction, it is washed and dried to obtain amino-modified polydopamine-coated nickel ferrite particles. The mass-to-volume ratio of dopamine-polymerized nickel ferrite to 3-aminopropyltriethoxysilane is 1g:3-5ml; The reaction conditions are a temperature of 60℃-78℃ and a time of 6-18h.
5. The method for preparing multi-level heterogeneous composite aerogel according to claim 1, characterized in that, The preparation method of monolayer MXene is as follows: LiF is dispersed in hydrochloric acid, and then Ti3AlC2 is added to react. After the reaction, the mixture is washed, sonicated, centrifuged and dried to obtain monolayer MXene. The mass ratio of LiF to Ti3AlC2 is 1-2:1; The reaction conditions are a temperature of 40-60℃ and a time of 12-36h.
6. The method for preparing multi-level heterogeneous composite aerogel according to claim 1, characterized in that, In S2, the mass ratio of 2,2-bis[4-(4-aminophenoxy)phenyl]propane to 3,3′,4,4′-biphenyltetracarboxylic dianhydride is 1:1-2, and the reaction is carried out under ice bath conditions for 2-4 hours. The mass ratio of graphene oxide, monolayer MXene, polyvinylpyrrolidone, amino-modified polydopamine-coated nickel ferrite particles, polyamic acid, and crosslinking agent in S3 is 0.065-0.095:0.03-0.06:0.01-0.04:0-0.08:0.45-1.25:0.05-0.35, and the amount of amino-modified polydopamine-coated nickel ferrite particles added is not zero; the pyrolysis treatment conditions are a temperature of 700-800℃, a time of 1-3h, and a heating rate of 1-3℃ / min; the crosslinking agent is one or more of glutaraldehyde, epichlorohydrin, and 1,4-bis(glycidoxy)butane.
7. A multi-level heterogeneous composite aerogel, characterized in that, The composite aerogel is prepared by the preparation method according to any one of claims 1-6.
8. The multi-level heterogeneous composite aerogel according to claim 7, characterized in that, The composite aerogel has a continuous three-dimensional porous network framework structure, in which NC / NFO particles are dispersed, and the NC / NFO particles have a core-shell structure; the composite aerogel contains FeNi alloy phase and Fe2O3 phase.
9. The application of the multi-level heterogeneous composite aerogel as described in claim 7 or 8 in electromagnetic wave absorption.
10. The application of the multi-level heterostructure composite aerogel as described in claim 7 or 8 in the adsorption of methylene blue.
